2014
DOI: 10.1017/s1751731114001876
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency to reach age of puberty and behaviour of buffalo heifers (Bubalus bubalis) kept on pasture or in confinement

Abstract: In order to evaluate the influence of rearing system (free-ranging (FR) v. confinement (C)) on buffalo heifer efficiency to reach age of puberty and on behavioural and immune functions, two experiments were conducted from September 2010 to October 2011. In Experiment I, 32 subjects aged 8 to 9 months at the start of experiment were used. A total of 16 animals (group C) were group housed in an indoor slatted floor pen (4 m 2 /animal) with an outdoor paddock (4 m 2 /animal); 16 others grazed on a Mediterranean n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
2
16
0
3
Order By: Relevance
“…In our study, 4 farms displayed values higher than 5.2 s, with 2 of them showing values higher than 6.3 s. The prevalence of animals lying partly or completely outside lying area was high with 40% of farms showing values above 33%. Previous results (De Rosa et al, 2009b;Sabia et al, 2014) showed that when available buffaloes tend to spend a high proportion of time in potholes, pools, or ponds. As only few farms had these facilities, we hypothesized that the buffaloes were induced to rest in more humid areas, such as the feeding alley, rather than in the resting area.…”
Section: Scores Of Animal-based Measurementsmentioning
confidence: 96%
“…In our study, 4 farms displayed values higher than 5.2 s, with 2 of them showing values higher than 6.3 s. The prevalence of animals lying partly or completely outside lying area was high with 40% of farms showing values above 33%. Previous results (De Rosa et al, 2009b;Sabia et al, 2014) showed that when available buffaloes tend to spend a high proportion of time in potholes, pools, or ponds. As only few farms had these facilities, we hypothesized that the buffaloes were induced to rest in more humid areas, such as the feeding alley, rather than in the resting area.…”
Section: Scores Of Animal-based Measurementsmentioning
confidence: 96%
“…Conversely, Terzano et al (1996) observed that grazing heifers reached puberty earlier than animals fed corn silage ad libitum, although the latter showed a higher weight at puberty. Similarly, Sabia et al (2014) found no significant differences in terms of age of puberty between buffalo heifers reared in intensive or extensive conditions, although the weights of puberty were higher in confined animals.…”
Section: Heifer Growth Phasementioning
confidence: 80%
“…However, these animals show a higher digestibility of protein and fibre as compared with cattle and sheep with lower emissions in the environment. When kept on pasture, buffalo heifers show productive and reproductive performances similar to those shown by confined animals whose diet is based on mixed rations (Sabia et al 2014). They eat a wide variety of plants, although they only occasionally ingest non-herbaceous plants; buffaloes are, therefore, considered grazers rather than browsers (Napolitano et al 2007).…”
Section: Feeding Behaviourmentioning
confidence: 84%
See 2 more Smart Citations